Penerapan Manajemen Risiko Pada Pembiayaan Di Bank Muamalat Indonesia (Bmi) Kantor Cabang Pembantu Pasuruan - Wakhidatus Sukria; Andriati Aziizah Syafitri; Naylatul Khoiriyah (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
This research discussed the Application Of Financing Risk Management at Bank Muamalat Indonesia (BMI) Pasuruan Sub-Branch Office. This type of research used is a qualitative research method. As for the data collection technique used by means of intervews to provide a systematic and accurate descrption of the application of risk management in financing at Bank Muamalat Indonesia KCP Pasuruan whose research focus is focused on the application of risk management and how to handle if a risk occurs in financing. The results of this study are: at Bank Muamalat Indonesia KCP Pasuruan in implementing financing risk management using several steps or stages such as the identification stage, the measurement stage, the monitoring stage and the control stage by applying good sharia principles for customers. In handling when there is a risk in financing Bank Muamalat Indonesia KCP Pasuruan uses procedures for the good of both parties. Starting from warnings to providing good solutions for these customers.